Eicosanoids and Oxidative Stress in Diabetic Retinopathy - Mong-Heng Wang; George Hsiao; Mohamed Al-Shabrawey (Antioxidants, 2020)
Oxidative stress is an important factor to cause the pathogenesis of diabetic retinopathy (DR) because the retina has high vascularization and long-time light exposition. Cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP) enzymes can convert arachidonic acid (AA) into eicosanoids, which are important lipid mediators to regulate DR development. COX-derived metabolites appear to be significant factors causative to oxidative stress and retinal microvascular dysfunction. Several elegant studies have unraveled the importance of LOX-derived eicosanoids, including LTs and HETEs, to oxidative stress and retinal microvascular dysfunction. The role of CYP eicosanoids in DR is yet to be explored. There is clear evidence that CYP-derived epoxyeicosatrienoic acids (EETs) have detrimental effects on the retina. Our recent study showed that the renin-angiotensin system (RAS) activation augments retinal soluble epoxide hydrolase (sEH), a crucial enzyme degrading EETs. Our findings suggest that EETs blockade can enhance the ability of RAS blockade to prevent or mitigate microvascular damage in DR. This review will focus on the critical information related the function of these eicosanoids in the retina, the interaction between eicosanoids and reactive oxygen species (ROS), and the involvement of eicosanoids in DR. We also identify potential targets for the treatment of DR.